In vitro evaluation of plant extracts and bioagents against Alternaria burnsii Uppal, Patel & Kamat causing blight of cumin (Cuminum cyminum L.) - B H Pipliya, K B Jadeja (Journal of Spices and Aromatic Crops, 2008)
Laboratory evaluation of 14 plant extracts for growth inhibition of Alternaria burnsii, thecausal organism of blight disease of cumin (Cuminum cyminum) indicated that 5% and 10%extract of garlic cloves and ginger rhizomes were most effective resulting in 78.52% and72.96% mean inhibition, respectively. Evaluation of 11 isolates of Trichoderma spp. against thepathogen in the laboratory indicated that T. harzianum 360 and T. viride Anand were mosteffective resulting in 100% inhibition of A. burnsii.